Study on the negative effect of internal-control willingness on enterprise risk-taking - Chen, Lijun; Li, Yanxi; Liu, Bin (Frontiers in Psychology, 2022)
In the traditional cognition, the factors affecting the level of internal control are usually based on the objective factors such as corporate characteristics, financial status and governance structure. However, the internal control defects of many famous companies expose the phenomenon of subjective manipulation, and this leads us to focus on the subjective factor of internal control, which we call internal-control willingness. We define “internal-control willingness” as the degrees of subjective initiative of the internal-control construction and execution activities. And we propose a method for measuring internal-control willingness, using text analysis and machine learning. Then we examine the impact of internal-control willingness on enterprise risk-taking, through the internal-control, financial and market data of China A-share main board enterprises in 2011-2016. The study found that: (1) Internal-control willingness has a significant positive impact on internal-control level, which can fairly achieve the measurement of internal-control subjective initiative. (2) It confirms that internal-control willingness lowers corporate risk-taking. This paper deepens the understanding of internal control and corporate strategic risk management, and suggests that the regulatory authorities actively urge the board of directors to strengthen the cultivation of internal-control willingness.